2023
DOI: 10.1093/biolre/ioad014
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid progesterone downregulated HPGD and COX2 in granulosa cells via suppressing NF-ĸB in endometriosis

Abstract: Increasing evidences showed ovulatory dysfunction, possibly caused by luteinized unruptured follicular follicle syndrome(LUFS), is one of the reasons for endometriosis-related infertility. The present study was conducted to explore the potential effect of elevated progesterone in follicular fluid (FF) on ovulation in endometriosis. A prospective study including 50 ovarian endometriosis patients and 50 control patients with matched pairs design was conducted with alterations in FF and peritoneal fluid (PF) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Effects of Glu and INS on GDM of two study groups up-regulated in FF of endometriosis patients[20]. Those data suggested dysregulated circulating metabolic molecules might play an important role in endometriosis development.…”
mentioning
confidence: 75%
“…Effects of Glu and INS on GDM of two study groups up-regulated in FF of endometriosis patients[20]. Those data suggested dysregulated circulating metabolic molecules might play an important role in endometriosis development.…”
mentioning
confidence: 75%
“…Both estrogen and progesterone levels considerably reduced following endometriotic fluid administration which could account for the observed drop in the diestrus phase and compromise in estrous cycle regularity. 25,26 Several studies looking at women with endometriotic have demonstrated that high LH secretion facilitates overproduction of ovarian androgens, which in turn is connected to heightened pituitary sensitivity to GnRH. Our study demonstrates that 2 mL/kg of endometriotic follicular fluid significantly increases LH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, metabolic approach has emerged as a possible non-invasive diagnostic tool in women with or without endometriosis [ 18 – 23 ]. Our previous study showed that most metabolites important for glucolipid metabolism were up-regulated in follicular fluid (FF) of endometriosis patients [ 24 ]. Those data suggested dysregulated circulating metabolic molecules might play an important role in endometriosis development.…”
Section: Discussionmentioning
confidence: 99%